Shape–color associations in an unrestricted color choice paradigm - Zelazny, Aurore; Liu, Xun; Sørensen, Thomas Alrik (Frontiers in Psychology, 2023)
Since Kandinsky’s claim for fundamental shape-color associations, several studies have revealed that those tendencies were not generalizable to the entire population, and that different associations were more prevalent. Past studies however lacked a methodology that allowed participants to freely report their shape-color preferences. Here we report data from 7517 Danish individuals, using a free choice full color-wheel for five different geometrical shapes. We find significant shape-hue associations for circle-red/yellow, triangle-green/yellow, square-blue and pentagon/hexagon-magenta. The significant shape-hue associations are also more saturated than non-significant ones for the circle, triangle and square. At the conceptual level, basic shapes, which show stronger associations, are linked to primary colors, and non-basic shapes to secondary colors. Shape-color associations seem indeed to follow the pattern of entry into languages described by Berlin and Kay (1969). This pattern had previously been described for graphemes and weekday-color associations. Our study offers an unrestricted paradigm for shape-color investigation, which can be repeated in different cultural contexts in the future. We also provide another instance of color associations for ordinal concepts that follow the stages of entry into languages.